The Effect of Alkali Treatment And Microcrystalline Cellulose Addition on Density Value of Cantala Fiber Reinforced Unsaturated Polyester Composites - Muhammad Ghozali; Dody Ariawan; Eko Surojo (Universitas Sebelas Maret, 2021)
Natural fiber reinforced composites is one material potentially developing in Indonesia. One of biggest problem with composites specimen is its void. One property to find out void of composites is composites density value. The objective of research is to investigate the effect of fiber alkali NaOH treatment and Microcrystalline Cellulose (MCC) addition on density value of cantala fiber reinforced unsaturated polyester composites. Firstly, cantala fibers was submerged into alkali NaOH 6% solution for 0, 3, 6, 9, and 12 hours. Furthermore, the fiber was washed using acetid acid and then using clean water to reach pH 7. Thereafter, cantala fiber was dried in the oven for 10 hours at temperature 60 ℃. Composites was composed of cantala fiber, unsaturated polyester polymer matrix, and microcrystalline cellulose according to the composition with volume fraction 30%. Composites was casted using compression molding method with compressive strength of 10 MPa for 12 hours. The result of research showed that the longer the alkali treatment time and the more addition of Microcrystalline Cellulose (MCC) filler, the higher is the composites density. The higher density value of cantala fiber reinforced unsaturated polyester is alkali treatment six hours, which was 1.223 gr/cm3.